A SHIFT IN THE ARTICULATION OF URBAN SOCIETY’S WORKING SPACE - Ayu, Ardianti Permata; Sulistyo, Danny Eko (International Review of Humanities Studies, 2020)
Swift technological development has caused shifting habits and changing behavioral pattern or lifestye in all respects, notably among urban society, including in terms of work and self-identity production. Members of society now have elevated flexibility to have their own working spaces. Work now can be carried out independently by a mere piece of gadget anywhere within the virtual room. It is co-working space which facilitates independent workers with a flexible, open-space, relaxed, cozy, entertaining, eye-catching, and now even instagrammable space organizing system. Now that plenty of co-working spaces have been produced, the spatial design of co-working space is gaining much popularity and setting a new trend for conventional office design. Taking a cultural study approach, this work examines how a shift in the meaning of work space takes place in urban settings from that of conventional offices to that of co-working spaces as a needs facility (functionally) and how the co-working space design model later becomes a trend in conventional office designing.